2012
DOI: 10.1111/j.1747-1346.2012.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Signals? Gender and the Media's Coverage of the 2008 Vice Presidential Candidates

Abstract: The 2008 presidential election was one of the most watched campaigns in American history, and prominently featured the vice presidential candidates, Governor Sarah Palin and Senator Joseph Biden. This election contest presents an exciting opportunity to expand and test our current understandings of the relationship between gender and media coverage. We examine this relationship using computer‐assisted content analysis of major newspapers, television news broadcasts, and political blogs. These three media are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…For example, Kahn () finds that while the media cover the candidacies of female U.S. Senate and gubernatorial candidates differently than their male counterparts, in both race types women receive less issue attention than their male colleagues, while in senatorial races women are also disadvantaged in the quantity and viability of coverage. And studies of presidential and vice presidential candidates Dole and Palin document differences in the volume (Dole receiving less and Palin more than male peers) and substance of coverage, roughly reflecting gender stereotypes (Bode and Hennings ; Heldman, Carroll, and Olson ). Ironically, scholars neglect analyses of U.S House candidacies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kahn () finds that while the media cover the candidacies of female U.S. Senate and gubernatorial candidates differently than their male counterparts, in both race types women receive less issue attention than their male colleagues, while in senatorial races women are also disadvantaged in the quantity and viability of coverage. And studies of presidential and vice presidential candidates Dole and Palin document differences in the volume (Dole receiving less and Palin more than male peers) and substance of coverage, roughly reflecting gender stereotypes (Bode and Hennings ; Heldman, Carroll, and Olson ). Ironically, scholars neglect analyses of U.S House candidacies.…”
Section: Methodsmentioning
confidence: 99%
“…One might assume that the content of campaign coverage differs little by medium. But recent research suggests otherwise (Bode and Hennings ). We know that, in absolute terms, newspapers tend to include more stories on state‐level elections than local television news programs—as producers rise to meet the viewing demands of different and often broader constituencies, which often span a variety of Congressional districts (Goldenberg and Traugott ; Jalalzai ).…”
mentioning
confidence: 99%
“…For example, a study of television, newspaper, and political blog coverage of the 2008 vice presidential candidates (Bode & Hennings, 2012) found that Palin received more than two times as much coverage as Biden and that the substance of her coverage was more likely to include discussions of her family (television and newspapers), her physical appearance (newspapers and blogs), her electability (blogs), and social issues (television, newspapers, and blogs). For example, a study of television, newspaper, and political blog coverage of the 2008 vice presidential candidates (Bode & Hennings, 2012) found that Palin received more than two times as much coverage as Biden and that the substance of her coverage was more likely to include discussions of her family (television and newspapers), her physical appearance (newspapers and blogs), her electability (blogs), and social issues (television, newspapers, and blogs).…”
Section: Media Coverage Of Female and Male Political Candidatesmentioning
confidence: 99%
“…However, other studies show that these disparities in media coverage among men and women politicians may be equalizing , showing similar amounts of coverage between men and women in more contemporary races (Jalalzai, 2006). Other studies have shown that in some races, women may actually receive more coverage than men (Bode & Hennings, 2012;Bystrom, Robertson, & Banwart, 2001). This evidence suggests there may not be a distinctive pattern in the quantity of coverage between men and women and that this coverage depends more on the political and electoral context (Bystrom, 2010).…”
Section: Gendered Differences In Media Coveragementioning
confidence: 97%
“…However, something that remains unclear is the differences that exist in the media's portrayal and construction of them. Previous research has documented the differences in media coverage between men and women in politics (Aday & Devitt, 2001;Bode & Hennings, 2012;Bystrom, 2010;Bystrom, Robertson, & Banwart, 2001;Carroll & Schreiber, 1997;Dolan, 2010;Falk, 2008;Kahn, 1994;Kahn & Goldenberg, 1991). Additionally, other research has begun to shed light on the differences between Republican and Democratic women in terms of their party's history (Baer, 2011;Baumgardner & Richards, 2000;Box-Steffensmeier, Chaney, Alvarez, & Nagler, 1998;Box-Steffensmeier, de Boef, & Lin, 2004;Kaufman & Petrocik, 1999;Klein, 1984a;Smeal, 1984;Mueller, 1988), personal policy stances (Shogan, 2001;Swers, 2002), and gender identification (Conover, 1988;Gurin, 1985;Schreiber, 2002).…”
Section: Introductionmentioning
confidence: 99%